Assessment of flood susceptibility mapping using support vector machine, logistic regression and their ensemble techniques in the Belt and Road region. Issue 25 (13th December 2022) - Liu, Jun; Wang, Jiyan; Xiong, Junnan; Cheng, Weiming; Li, Yi; Cao, Yifan; He, Yufeng; Duan, Yu; He, Wen; Yang, Gang
Abstract: Floods have occurred frequently all over the world. During 2000–2020, nearly half (44.9%) of global floods occurred in the Belt and Road region because of its complex geology, topography, and climate. Therefore, providing an insight into the spatial distribution characteristics of flood susceptibility in this region is essential. Here, a database was established with 11 flood conditioning factors, 1500 flooded points, and 1500 non-flooded points selected by an improved method. Subsequently, a rare combination of logistic regression and support vector machine, integrated by heterogeneous framework, was applied to generate an ensemble flood susceptibility map. Based on it, the concept of ecological vulnerability synthesis index in the ecological field was introduced into this study, and the flood susceptibility comprehensive index (FSCI) was proposed to quantify the degree of flood susceptibility of each country and sub-region. At the results, the ensemble model has an excellent accuracy, with the highest AUC value of 0.9342. The highest and high flood susceptibility zones are mainly located in the southeastern part of Eastern Asia, most of Southeast Asia and South Asia, account for 12.22% and 9.57% of the total study area, respectively. From the regional perspective, it can be found that Southeast Asia had the highest flood susceptibility with the highest FSCI of 4.69, while East Asia and Central and Eastern Europe showed the most significant spatial distribution characteristics. From the national perspective, of the 66 countries in this region, 20 of the countries have the highest flood susceptibility level (FSCIn > 0.8), which face the greatest threat of flooding. These results are able to facilitate reasonable flood mitigation measures develop at the most critical locations in the Belt and Road region and lays a theoretical basis for quantifying flood susceptibility at national or regional scale.